Key Properties of Graphene and its Application in Functional Materials - Liu Donghao (MATEC Web of Conferences)
Graphene, a two-dimensional honeycomb crystal material composed of sp²-hybridized carbon atoms, has garnered extensive attention in materials science since its preparation by mechanical exfoliation in 2004, owing to its unique physical properties (such as ultrahigh carrier mobility and negative Poisson’s ratio). This paper analyzes systematically the microscopic mechanisms of graphene’s negative Poisson’s ratio. It focuses on the regulatory effects of chemical modification and heterostructures on its mechanical response. The study reveals that the negative Poisson’s ratio behavior of graphene springs from strain transmission in its two-dimensional lattice through bond angle distortions under stress. Furthermore, surface functionalization enables continuous tuning of the Poisson’s ratio within the range of -0.6 to 0.4. Additionally, graphene’s Dirac cone band structure endows it with room-temperature quantum Hall effects and Klein tunneling, and the coupling of these quantum properties with its anomalous mechanical behavior has led to groundbreaking applications such as ultrasensitive strain sensors, flexible electronic skins, and topological quantum devices. This paper also establishes a “structure-property-application” synergistic design framework, providing theoretical support for developing next-generation smart composite materials. The result of research shows that graphene holds immense potential for applications in composite materials, flexible electronics, and energy storage. However, its large-scale application still needs to solve critical challenges, including interfacial coupling mechanisms and multiscale structural regulation.